Cultural adaptation of a children's weight management programme for Bangladeshi and Pakistani families in the UK: a cluster-randomised feasibility study protocol. Issue 1 (December 2016) - Pallan, Miranda; Griffin, Tania; Lancashire, Emma; Hurley, Kiya; Blissett, Jacqueline; Frew, Emma; Gill, Paramjit; Griffith, Laura; Hemming, Karla; Jolly, Kate; McGee, Eleanor; Mulhern, Charlene; et al.
Abstract Background Group-based children's weight management programmes are widely available in the UK and evidence shows that these are effective in the short-term. No programmes have been specifically developed to meet the cultural requirements of UK minority ethnic communities. South Asian children are a high-risk group for obesity and its consequences; therefore, the study aim is to adapt an existing weight management programme for children aged 4-11 years and their families to ensure cultural relevance to Pakistani and Bangladeshi communities, and undertake a feasibility study of the adapted programme. Methods/design Pakistani and Bangladeshi families of overweight children who have been offered the existing children's weight management programme in Birmingham, UK, will be invited to interviews and focus groups to explore their experiences and views of the programme. These data, together with existing literature and service provider information, will inform adaptation of the programme to be more culturally relevant to these families. The feasibility study will employ a cluster-randomised design, and will assess success of programme adaptation and feasibility of programme delivery. Planned programmes will be randomised to be delivered as the adapted programme (intervention) or the standard programme (comparator) with a 2:1 ratio. The primary outcome will be the proportion of Pakistani and Bangladeshi families completing the adapted programme. To assess recruitment, retention and data collection methods to inform a future trial, we aim to recruit 80 participants. A range of assessments will be undertaken with participants pre-, post- and 6-months post-intervention. Discussion This study addresses the identified need to provide children's weight management programmes that are suitable for minority ethnic communities. Whilst the focus of the intervention adaptation is on Pakistani and Bangladeshi communities, the programme will be developed to be flexibly delivered to meet the cultural needs of communities of all ethnic compositions. The feasibility study will directly compare the adapted and existing weight management programmes, and will enable a comprehensive evaluation of the success of the adaptation. Essential information will also be gathered to inform the design and sample size calculation of a future trial to evaluate intervention effectiveness. Trial registration ISRCTN81798055, registered: 13/05/2014.